Binder, positive electrode material slurry, positive plate and battery

By using modified hydrogenated nitrile rubber as a binder in lithium batteries, the ratio of flexible monomers is optimized, and the problem of easy cracking of the coating of thick electrodes of lithium batteries is solved, and the safety and reliability of the battery are improved.

CN119709049APending Publication Date: 2025-03-28ZHONGTIAN ENERGY STORAGE TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411933384.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing lithium batteries are prone to cracking in the coating and processing of medium-thick electrodes, which leads to "skinning" problems and hinders the application of ultra-high energy density batteries.

Method used

Modified hydrogenated nitrile rubber is used as the binder to improve the crack resistance of the electrode sheet by optimizing the proportion of flexible monomers and polymeric ester monomers.

Benefits of technology

The structural stability and crack resistance of the electrode sheet are improved, and the safety and reliability of lithium batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709049A_ABST
    Figure CN119709049A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, in particular to a binder, positive electrode material slurry, a positive plate and a battery. The binder comprises modified hydrogenated butadiene-acrylonitrile rubber; the structural formula of the modified hydrogenated butadiene-acrylonitrile rubber is # imgabs0 #; wherein the ratio of x to y is (0.4-1.5): 1; m is any integer from 1 to 3; r is a substituted or unsubstituted ester group. According to the invention, the modified hydrogenated nitrile rubber with excellent bonding performance and flexibility is adopted as the binder, so that the anti-cracking performance of the pole piece is improved, and the safety and reliability of the lithium battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a binder, a positive electrode material slurry, a positive electrode sheet and a battery. Background Art

[0002] Secondary batteries are widely used due to their renewable and reusable characteristics. They are favored by commercial and civilian users for their excellent long life, safety performance and cost advantages. With the development and progress of science and technology, various types of batteries are produced to meet market demand. At present, people are paying more and more attention to the battery's mileage and service life, and the demand for large-capacity and long-life batteries is increasing. At present, lithium-ion batteries still occupy one of the mainstream markets. Lithium-ion batteries mainly consist of four main materials, including positive electrode, negative electrode, diaphragm, electrolyte, conductive agent, binder and other auxiliary materials, as well as shell structure. During the use of lithium batteries, lithium ions migrate back and forth between the positive and negative electrodes to form charging and discharging.

[0003] For large-capacity, long-life lithium batteries, engineers use a high-coating electrode to improve energy density. However, the coating process of thick electrodes is prone to cracking, and in severe cases, even "peeling" problems occur, which hinders the application of thick electrodes in ultra-high energy density batteries. Therefore, the coating cracking and "peeling" problems are problems that need to be solved urgently in this field. Summary of the invention

[0004] In order to solve the above problems in the prior art, the present invention provides a binder, a positive electrode material slurry, a positive electrode sheet and a battery, wherein modified hydrogenated nitrile rubber is used as a binder, which helps to improve the anti-cracking performance of the electrode sheet through its excellent bonding performance and flexibility, thereby improving the safety and reliability of the lithium battery.

[0005] Based on this, the present invention has the following technical solutions: In a first aspect, the present invention provides a binder, comprising a modified hydrogenated nitrile rubber; the structural formula of the modified hydrogenated nitrile rubber is: ; Where, x:y=(0.4~1.5):1; m is any integer from 1 to 3; R is a substituted or unsubstituted ester group.

[0006] In the preparation of lithium battery pole pieces, the selection of binders is crucial to the mechanical and electrochemical properties of the pole pieces. At present, polyvinylidene fluoride is commonly used as the positive electrode binder. This glue uses van der Waals force to bond powder and foil, and has good bonding performance, but the pole piece is relatively hard and brittle, especially when thick electrodes are coated, the pole piece cracks, the material is broken off in the wound battery positive pole piece, and even breaks occur from time to time. The present invention finds that by adjusting the proportion of flexible monomers and polymerized ester monomers, the flexibility of the rubber is greatly optimized, and the coating and the material breaking conditions in the pole piece are improved. The amount of flexible monomer polymerization increases, and the flexibility of the glue and the pole piece is optimized, but there are too many soft monomers. As the battery is charged and discharged, the stability of the pole piece structure is poor, the battery impedance increases, and the cycle capacity retention is affected.

[0007] In the present invention, R may be a substituted or unsubstituted ester group having 1 to 8 carbon atoms, wherein when substituted, the substituent may be an alkenyl group, a carboxyl group, an alkyl group, a hydroxyl group, and the like.

[0008] Preferably, R comprises methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate or 2-hydroxypropyl acrylate.

[0009] Preferably, m is 1.

[0010] Preferably, x:y=(0.7~1.2):1, for example, it can be 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1 or 1.2:1.

[0011] The present invention finds that the modified hydrogenated nitrile rubber having the above structure can have both excellent bonding performance and flexibility, and further enhance the structural stability and crack resistance of the pole piece.

[0012] Preferably, the preparation method of the modified hydrogenated nitrile rubber comprises: (1) Mix water, emulsifier and acrylonitrile monomer at 35-45° C. and stir until acrylonitrile is completely emulsified to obtain a first mixed solution; (2) mixing and stirring the emulsifier, butadiene monomer and the first mixed liquid to obtain a second mixed liquid; (3) Add the second mixed solution Mix and stir to obtain a third mixed solution; (4) mixing the third mixed liquid with an initiator, a cross-linking agent, and a regulator, and performing a polymerization reaction to obtain a reaction liquid; (5) The reaction solution is mixed with the catalyst, and stirred for 5 to 10 hours under the conditions of hydrogen, 5.0 to 8.0 MPa, and 100 to 180° C.

[0013] Preferably, the emulsifier includes one or more of sodium laurate, sodium oleate, sodium lauryl sulfate, sodium lauryl polyoxyethylene sulfate, sodium hexadecyl sulfonate and propylene glycol fatty acid ester.

[0014] Preferably, the initiator comprises one or more of benzoyl peroxide, dilauroyl peroxide, tert-butyl perbenzoate, potassium persulfate, sodium persulfate and ammonium persulfate.

[0015] Preferably, the cross-linking agent includes one or more of divinylbenzene, diisocyanate, methylenebisacrylamide, polyethylene glycol and p-toluenesulfonic acid.

[0016] Preferably, the regulator includes one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and tetrahydrofuran.

[0017] Preferably, the catalyst comprises one or more of a palladium-type catalyst, a rhodium-type catalyst, and tris(sodium diphenylphosphine-m-sulfonate)rhodium chloride.

[0018] In the present invention, those skilled in the art can select the dosage of emulsifier, initiator, cross-linking agent, regulator and catalyst as needed, or use the dosage conventionally used in the art.

[0019] In a second aspect, the present invention provides a positive electrode material slurry, which includes the above-mentioned binder.

[0020] Preferably, based on the total mass of the positive electrode material slurry, the content of the binder is 1wt%~3wt%, for example, it can be any value among 1wt%, 1.5wt%, 2wt%, 2.5wt% and 3wt%, or a numerical range with any two of the above values ​​as endpoints.

[0021] Preferably, the positive electrode material slurry comprises a positive electrode active material, a conductive agent, the binder according to any one of claims 1 to 5, and a solvent.

[0022] In the present invention, the positive electrode active material can be lithium iron phosphate (LFP), lithium cobalt oxide (LiCoO2, abbreviated as LCO), lithium manganese oxide (LiMn2O4, abbreviated as LMO), ternary material (lithium nickel cobalt manganese oxide LiNi1-x-yCoxMnyO2, abbreviated as NCM), lithium nickel cobalt aluminum oxide (LiNi1-x-yCoxAlyO2, abbreviated as NCA), high-voltage lithium nickel manganese oxide (LNMO), lithium manganese iron phosphate (LMFP) and lithium-rich manganese-based layered materials, etc., without limitation herein.

[0023] In the present invention, the conductive agent includes one of carbon black, carbon nanotubes, graphene and carbon fiber tubes; and the solvent includes N-methylpyrrolidone (NMP).

[0024] Preferably, the positive electrode material slurry comprises the following components in parts by weight: Lithium iron phosphate 90~98 parts; Carbon black 0.5~1.5 parts; 0.3-0.8 parts of carbon nanotubes; Modified hydrogenated nitrile rubber 1-3 parts; 30-50 parts of N-methylpyrrolidone.

[0025] In a third aspect, the present invention provides a positive electrode sheet, which includes a current collector and an active layer on the surface of the current collector; the active layer is made of the positive electrode material slurry.

[0026] In the present invention, the current collector includes conventional current collectors such as copper foil, aluminum foil, nickel foam or nickel foil, which are not limited here.

[0027] Preferably, the method for preparing the positive electrode sheet comprises: coating the positive electrode material slurry on the surface of the current collector, then baking at 90-100° C., and preparing the positive electrode sheet through rolling, slitting and die-cutting.

[0028] Preferably, the surface density of the positive electrode material slurry coated on the surface of the current collector is 300-800 g / cm 2 ; Further preferably 300 ~ 450g / cm 2 ; Specifically, it can be 300g / cm 2 、350g / cm 2 , 400g / cm 2 and 450g / cm 2 Any value in ; or, a numerical range in which any two of the above values ​​are endpoints.

[0029] In a fourth aspect, the present invention provides a battery comprising the positive electrode sheet.

[0030] The present invention provides a binder, a positive electrode material slurry, a positive electrode sheet and a battery. By using modified hydrogenated nitrile rubber with excellent bonding performance and flexibility as a binder, it is helpful to improve the anti-cracking performance of the electrode sheet, thereby improving the safety and reliability of the lithium battery. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.

[0033] Example 1 This embodiment provides a positive electrode material slurry, and the preparation method thereof includes the following steps: The positive electrode active material LFP, conductive carbon black, carbon nanotubes, and modified hydrogenated nitrile rubber were mixed in a mass ratio of 96.5:1:0.5:2.0, and NMP was used as a solvent (with a concentration of 50%). The mixture was added into a vacuum mixer and stirred evenly.

[0034] Wherein, the structural formula of the modified hydrogenated nitrile rubber is , R is , x:y=1.5:1; m=1; molecular weight is 650,000-800,000, and the preparation method comprises the following steps: (1) 1 kg of deionized water, 11.2 g of sodium hexadecyl sulfate, and 37 g of acrylonitrile monomer were added to a 5 L reactor in sequence, and nitrogen was introduced after evacuation. The mixture was heated to 35° C. and stirred until the acrylonitrile was completely emulsified to obtain a first mixed solution. (2) adding 4.5 g of propylene glycol fatty acid ester and 26.3 g of butadiene monomer, mixing and stirring at a constant temperature for 30 min to obtain a second mixed solution; (3) Add 8.8g of Mix and stir to obtain a third mixed solution; (4) Add 1.2 g of sodium persulfate, 10.1 g of p-toluenesulfonic acid and 1.3 g of n-dodecyl mercaptan to the third mixed solution, stir and mix to react for 1 h, then transfer to an autoclave, evacuate and introduce nitrogen, add 7 g of palladium catalyst and introduce hydrogen, stir at 7 MPa and 120°C for 8 h to obtain modified hydrogenated nitrile rubber.

[0035] This embodiment further provides a positive electrode sheet, and the preparation method thereof comprises the following steps: Take out the above slurry and mix it at 350g / cm 2 The surface density is coated on 13um carbon-coated aluminum foil and then baked at 90°C. The positive electrode sheet is prepared by rolling, slitting and die cutting.

[0036] Example 2 This embodiment provides a positive electrode material slurry, which differs from Embodiment 1 only in that: x:y=1.2:1; m=1; molecular weight is 650,000-800,000. Its preparation method is substantially the same as that of Embodiment 1, except that the modified hydrogenated nitrile rubber in this embodiment is obtained by adjusting the mass ratio of acrylonitrile and butadiene.

[0037] This embodiment further provides a positive electrode sheet, and its preparation method is the same as that of embodiment 1.

[0038] Example 3 This embodiment provides a positive electrode material slurry, which differs from Embodiment 1 only in that: x:y=0.7:1; m=1; molecular weight is 680,000-850,000. Its preparation method is substantially the same as that of Embodiment 1, except that the modified hydrogenated nitrile rubber in this embodiment is obtained by adjusting the mass ratio of acrylonitrile and butadiene.

[0039] This embodiment further provides a positive electrode sheet, and its preparation method is the same as that of embodiment 1.

[0040] Example 4 This embodiment provides a positive electrode sheet, using the positive electrode material slurry prepared in Example 2. The difference between the preparation method and Example 2 is that the coating surface density is 450g / cm 2 .

[0041] Example 5 This embodiment provides a positive electrode sheet, using the positive electrode material slurry prepared in Example 3. The difference between the preparation method and that of Example 3 is that the coating surface density is 700 g / cm 2 .

[0042] Example 6 This embodiment provides a positive electrode material slurry, which differs from the embodiment 1 only in that: x:y=0.7:1; m=3; molecular weight is 700,000-1.1 million, and the preparation method thereof comprises the following steps: (1) 1 kg of deionized water, 11.2 g of sodium hexadecyl sulfate, and 37 g of acrylonitrile monomer were added to a 5 L reactor in sequence, and nitrogen was introduced after evacuation. The mixture was heated to 35° C. and stirred until the acrylonitrile was completely emulsified to obtain a first mixed solution. (2) adding 10.3 g of propylene glycol fatty acid ester and 53.2 g of butadiene monomer, mixing and stirring at a constant temperature for 30 min to obtain a second mixed solution; (3) Add 29.1g of Mix and stir to obtain a third mixed solution; (4) Add 1.5 g of sodium persulfate, 13.2 g of p-toluenesulfonic acid and 1.7 g of n-dodecyl mercaptan to the third mixed solution, stir and mix to react for 1 h, then transfer to an autoclave, evacuate and introduce nitrogen, add a catalyst and introduce hydrogen, and stir at 7 MPa and 120°C for 8 h to obtain modified hydrogenated nitrile rubber.

[0043] This embodiment further provides a positive electrode sheet, the preparation method of which is different from that of embodiment 1 only in that: the coating surface density is 700 g / cm 2 .

[0044] Example 7 This embodiment provides a positive electrode material slurry, which differs from Embodiment 1 only in that: x:y=0.4:1; m=3; molecular weight is 700,000-1.1 million, and its preparation method is substantially the same as that of Embodiment 1, except that the modified hydrogenated nitrile rubber in this embodiment is obtained by adjusting the mass ratio of acrylonitrile and butadiene.

[0045] This embodiment further provides a positive electrode sheet, the preparation method of which is different from that of embodiment 1 only in that: the coating surface density is 700 g / cm 2 .

[0046] Comparative Example 1 This comparative example provides a positive electrode material slurry, which differs from Example 1 only in that: x:y=1:1; m=0; the molecular weight is 630,000-780,000, and the preparation method thereof comprises the following steps: (1) 1 kg of deionized water, 11.2 g of sodium hexadecyl sulfate, and 37 g of acrylonitrile monomer were added to a 5 L reactor in sequence, and nitrogen was introduced after evacuation. The mixture was heated to 35° C. and stirred until the acrylonitrile was completely emulsified to obtain a first mixed solution. (2) adding 10.3 g of propylene glycol fatty acid ester and 53.2 g of butadiene monomer, mixing and stirring at a constant temperature for 30 min to obtain a second mixed solution; (3) Add 1.0 g of sodium persulfate, 10.2 g of p-toluenesulfonic acid and 1.1 g of n-dodecyl mercaptan to the second mixed solution, stir and mix to react for 1 h, then transfer to an autoclave, evacuate and introduce nitrogen, add a catalyst and introduce hydrogen, and stir at 7 MPa and 120°C for 8 h to obtain hydrogenated nitrile rubber.

[0047] This comparative example further provides a positive electrode sheet, the preparation method of which is different from that of Example 1 only in that: the coating surface density is 450 g / cm 2 .

[0048] Test example The present invention further assembles the positive electrode sheet, negative electrode sheet and separator prepared in the above embodiments and comparative examples, and tests the performance of the assembled battery: Specifically include: Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber were mixed in a mass ratio of 96:1:1.2:1.8, deionized water was used as solvent, and added to a vacuum mixer. After being stirred evenly, 180g / cm2 surface density was coated on 8um copper foil and baked at 80°C. The negative electrode sheet was prepared by rolling, slitting and die cutting.

[0049] The prepared positive and negative electrode sheets are placed in a stacking machine, stacked with 16um PE diaphragm, welded to the tabs, encapsulated in aluminum-plastic film, and injected with electrolyte after baking and moisture content is qualified. The electrolyte components mainly include LiPF6, EC, DMC, EMC, VC and other additives. After packaging, formation, aging, capacity separation, aging and other processes, the battery preparation is completed.

[0050] Pole piece crack detection: Apply wet film and bake at 90℃ to observe whether the material area is cracked. If there is no crack, then use a 2mm diameter winding needle to wind the pole piece and observe whether it is cracked.

[0051] After the battery is prepared, the electrochemical performance test is carried out to measure the internal resistance and cycle performance, and to follow up the battery capacity retention rate during the cycle overcharge. The cycle test is carried out at 45°C, charging to 3.65V at 1.0P constant power, standing for 10 minutes, and discharging to 2.5V at 1.0P constant power. This is the cycle, and the cycle is set to 2000 cycles.

[0052] The results are shown in Table 1: Table 1

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A binder, characterized in that: Including modified hydrogenated nitrile rubber; The structural formula of the modified hydrogenated nitrile rubber is: ; Where, x:y=(0.4~1.5):1; m is any integer from 1 to 3; R is a substituted or unsubstituted ester group.

2. The adhesive according to claim 1, characterized in that R includes methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate or 2-hydroxypropyl acrylate.

3. The adhesive according to claim 1 or 2, characterized in that: m is 1.

4. The adhesive according to any one of claims 1 to 3, characterized in that x:y=(0.7~1.2):

1.

5. According to the binding agent described in any one of claims 1 to 3, the preparation method of the modified hydrogenated nitrile rubber comprises: (1) Mix water, emulsifier and acrylonitrile monomer at 35-45° C. and stir until acrylonitrile is completely emulsified to obtain a first mixed solution; (2) mixing and stirring the emulsifier, butadiene monomer and the first mixed liquid to obtain a second mixed liquid; (3) Add the second mixed solution Mix and stir to obtain a third mixed solution; (4) mixing the third mixed liquid with an initiator, a cross-linking agent, and a regulator, and performing a polymerization reaction to obtain a reaction liquid; (5) mixing the reaction solution with the catalyst, and stirring for 5 to 10 hours under the conditions of hydrogen, 5.0 to 8.0 MPa, and 100 to 180° C.; Preferably, the emulsifier includes one or more of sodium laurate, sodium oleate, sodium lauryl sulfate, sodium lauryl polyoxyethylene sulfate, sodium hexadecyl sulfonate and propylene glycol fatty acid ester; Preferably, the initiator comprises one or more of benzoyl peroxide, dilauroyl peroxide, tert-butyl perbenzoate, potassium persulfate, sodium persulfate and ammonium persulfate; Preferably, the cross-linking agent comprises one or more of divinylbenzene, diisocyanate, methylenebisacrylamide, polyethylene glycol and p-toluenesulfonic acid; Preferably, the regulator includes one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and tetrahydrofuran; Preferably, the catalyst comprises one or more of a palladium-type catalyst, a rhodium-type catalyst, and tris(sodium diphenylphosphine-m-sulfonate)rhodium chloride.

6. A positive electrode material slurry, characterized in that: The invention comprises the adhesive according to any one of claims 1 to 5.

7. The positive electrode material slurry according to claim 6, characterized in that: Based on the total mass of the positive electrode material slurry, the content of the binder is 1wt%~3wt%.

8. The positive electrode material slurry according to claim 6, characterized in that: The positive electrode material slurry comprises a positive electrode active material, a conductive agent, a binder according to any one of claims 1 to 5, and a solvent; preferably, the positive electrode material slurry comprises the following components in parts by weight: Lithium iron phosphate 90~98 parts; Carbon black 0.5~1.5 parts; 0.3-0.8 parts of carbon nanotubes; Modified hydrogenated nitrile rubber 1-3 parts; 30-50 parts of N-methylpyrrolidone.

9. A positive electrode sheet, characterized in that: It comprises a current collector and an active layer on the surface of the current collector; the active layer is made of the positive electrode material slurry according to any one of claims 6 to 8.

10. A battery, characterized in that: It includes the positive electrode sheet as claimed in claim 9.